The implementation of Deming’s theory of quality management in Greek public admin-istration - Σιούτου, Αναστασία (Πανεπιστήμιο Πελοποννήσου, 2020)
The primary purposes of this study were: (a) to evaluate to what extent the Deming Management Method is being implemented in Greek Public Administration; (b) to ex-amine to what extent the administrative executives of Greek Public Administration be-lieve that Deming Management Method adds value to the organizations of Greek Public Administration; (c) to study to what extent the administrative executives of Greek Pub-lic Administration have the intention to implement Deming’s Management Method in their organizations in the future; (d) to investigate to what extent the administrative ex-ecutives of Greek Public Administration are satisfied from the level of organizational performance as measured by satisfaction levels in relation to the key performance indica-tors of their organizations (goals, human resource, suppliers, improvements) and (e) to examine the relationship between the key factors of Deming Management Method (Deming on People, Deming on Leadership, Deming on Education and Training, Dem-ing on Suppliers and Deming on Systems) and the key performance indicators (goals, human resource, suppliers, improvements) of the abovementioned organizations. The questionnaire of Deming Management Method, consisted of 59 questions developed by (Kriemadis & Sioutou, 2019), and demographic characteristics. Valid questionnaires were received from 334 senior and junior level public administrators of Greek public administration. The findings of this study were as follows: 1. Deming Management Method is applied to a mediocre extent in Greek Public Administration; 2. The adminis-trative executives of Greek Public Administration believe in a great extent that Deming Management Method adds value to the organizations of Greek Public Administration; 3. The administrative executives of Greek Public Administration have in a great extent the intention to implement Deming’s Management Method in their organizations in the fu-ture; 4. Medium level of satisfaction of the administrative executives was found con-cerning the organizational performance in the abovementioned organizations as meas-ured by satisfaction levels in relation to the key performance indicators of their organiza-tions (goals, human resource, suppliers, improvements); 5. There was a strong and posi-tive relationship between the key factors of Deming Management Method and the spe-cific key performance indicators of the questionnaire, that measure the performance of public administration organizations, through the satisfaction level of the administrative executives of public administration, except the key factor “Deming on Systems”.
Η Εφαρμογή της Θεωρίας του Deming σχετικά με την Διοίκηση Ποιότητας στην Ελληνική Δημόσια Διοίκηση
Keywords: Δημόσια διοίκηση - Ελλάδα; Διοίκηση ολικής ποιότητας; Public administration - Greece; Total quality management; Quality management; Deming management method; Greek public administration; Διοίκηση ποιότητας; Μέθοδος διοίκησης του deming; Ελληνική δημόσια διοίκηση